Development of Curriculum Evaluation Model As A Foundation in Strengthening The Ideology of Al-Irsyad Education - Subando, Joko; Kartawagiran, Badrun; Munadi, Sudji (Universitas Negeri Semarang, 2021)
Curriculum evaluation models are useful to ensure designs, processes, and products follow the ideology of Education. This study aims to develop the Al-Irsyad curriculum evaluation model to strengthen the educational ideology (EKADIOLOGI). This research used the ADDIE model. The analysis activity was to see the need for an evaluation model. The initial product was developed by confirming 11 experts, practitioners, and model users. The limited trial involved 159 respondents and 492 respondents in the expanded test phase. The data of instrument model test results, the model use guide, the feasibility of the model, and the assessment of the readability of the instrument were analyzed using Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA) to get an overview of the validity of the instrument and Cronbach Alpha for estimating its reliability. The conclusion of the study is EKADIOLOGI consists of four constructs encompassing design, process, output, and, outcome. The fit model is supported by empirical data with a Chi-square probability value of 0.08846 (> 0.05), RMSEA value of 0.049 (<0.08), an NFI value of 0.93 (> 0.9), and CFI of 0.98 (> 0.9). The EKADIOLOGI model instrument has good validity and guaranteed reliability so that the model can be recommended for curriculum evaluation in Al-Irsyad schools. The results of this study can be used as an instrument of curriculum evaluation in Al-Irsyad schools and a foundation for strengthening the ideology of Al-Irsyad Education.